Ecophysiological determinants of Oregano productivity: eﬀects of plant’s canopy architecture on radiation capture and use, biomass partitioning and essential oil yield - Davidenco, Vanina; Pelissero, Pablo J.; Argüello, Juan A.; Vega, Claudia Rosa Cecilia (Elsevier, 2021)
This research aimed at studying oregano crop responses to changes in planting patterns in terms of solar radiation capture (c-PAR) and use (RUE), carbon partitioning, and essential oil yield (EO). O. vulgare ssp. vulgare (OVV) and O. vulgare ssp hirtum (OVH), with creeping and erect growth habits respectively, were grown during two consecutive cycles (C) under contrasting planting patterns (PP): T (0.70m between rows and 0.20m between plants) and H (0.35m×0.40m). Temporal dynamics ofbiomass accumulation varied between subspecies, and signiﬁcant interactions were found between PP and C. Crop growth rates (CGR) were highest in C1 (5 to 9.5gm−2 d-1).SigniﬁcantCGRdecreasesinC2wereexplainedbydropsinRUE(≅54%),whichinturncouldbe attributed to increases in the stem proportion in detriment to photosynthetic tissues. Among subspecies, OVV exhibited the highest plasticity for light capture, use and growth. Phenological progress along with c-PAR explained EO productivity. On average, reproductive phenophases yielded almost four times more than vegetative ones, and OVV yielded 30 % more EO than OVH. EO diﬀerences between subspecies could be explained by the partition to harvestable organs (Leaf+Flowers). This ecophysiological analysis presents a novel approach to disentangle the eﬀects of interactions between canopy architecture (subspecies), management and crop age on processes that regulate yield formation in Oregano.